Pengaruh Good Corporate Governance (GCG) dan Profitabilitas Terhadap Nilai Perusahaan pada Perusahaan Sektor Infrastruktur - Nurlita Hairunnisa; Ina Khodijah; Mochamad Fahru Komarudin (Kajian Ekonomi dan Akuntansi Terapan, 2025)
The concept of company value is critical for investors as it reflects the potential growth, profitability, and long-term sustainability of a business. Company value is a critical factor that guides investment decisions, as it embodies both tangible and intangible factors that contribute to the firm’s success. The factors that influence company value include Good Corporate Governance (GCG), which refers to the practices that ensure a company’s management is held accountable, transparent, and efficient. It also includes profitability metrics, such as Return on Assets (ROA) and Return on Equity (ROE), which indicate how well a company is performing in generating profits from its assets and equity. This study aimed to analyze how GCG and profitability influence company value, specifically in the infrastructure sector of Indonesia, listed on the Indonesia Stock Exchange (IDX). By using multiple linear regression analysis with data collected from 8 companies between 2020 and 2024, the research uncovered some insightful findings. It was found that the presence of Independent Commissioners, as part of GCG, had a positive and significant effect on company value. This highlights the importance of having independent oversight to ensure that the company operates in the best interests of its shareholders. In contrast, Institutional Ownership had no significant impact on company value, which might suggest that larger institutional investors do not always influence the company’s strategic direction in a way that directly affects value. Additionally, profitability, as measured by ROA and ROE, had significant effects on company value. ROA negatively influenced company value, which may indicate that companies with higher assets do not always perform better in terms of profitability, possibly due to inefficiencies. However, ROE had a positive influence on company value, suggesting that companies that efficiently use equity to generate profits are viewed more favorably by investors.